The Role Customer Relationship Marketing, Service Quality, Brand Image, and Customer Satisfaction in Customer Loyalty in FMCG Industry - Fitriani, Nani; Yafie, Muhammad Fauzan; Laksamana, Patria (Research Center and Case Clearing House PPM School of Management, 2025)
Amid the intense competition in the Fast-Moving Consumer Goods (FMCG) industry, companies must continuously seek ways to build long-term relationships with customers to maintain their loyalty. Customer Relationship Marketing (CRM), service quality, brand image, and customer satisfaction are key factors in sustaining customer loyalty. This study aims to analyze the influence of CRM, service quality, brand image, and customer satisfaction on customer loyalty in Indonesia's FMCG industry. This study employed a quantitative method with a sample of 100 respondents in Jakarta representing FMCG consumers. Data were collected through questionnaires distributed to FMCG users in Jakarta. The collected data were processed using SPSS before further analysis. Statistical test results show that the CRM variable has a significant positive correlation with customer loyalty. The service quality variable also has a significant positive correlation with customer loyalty. In contrast, the findings reveal that the brand image variable does not have a positive correlation and does not influence customer loyalty. Similarly, the customer satisfaction variable shows no positive correlation and no significant or strong relationship with customer loyalty. However, CRM, brand image, service quality, and customer satisfaction, simultaneously, have a significant and positive effect on customer loyalty.